Intestinal B cell hyperactivity in AIDS is controlled by highly active antiretroviral therapy - Nilssen, D E (Copyright 2004 by Gut, 2004)
Background: It is well documented that highly active antiretroviral therapy (HAART) restores systemic immunity to human immunodeficiency virus (HIV) but the effect of this treatment on the mucosal immune system is less clear. Aims: Because future preventive or therapeutic vaccines against HIV may be administered by the mucosal route, we wished to evaluate the effect of HAART on the activation level and homeostasis of the intestinal B cell system. Patients and methods: Duodenal biopsy specimens were collected consecutively from infection prone HIV positive adults (n = 31), mostly with advanced AIDS. In situ two colour immunofluorescence staining was performed to quantify mucosal immunoglobulin (Ig) class and subclass producing immunocytes (plasmablasts and plasma cells). Results: HIV positive patients had, on average, duodenal proportions of IgA (74.6%), IgM (19.5%), and IgG (3.4%) immunocytes similar to median values recorded in 11 HIV seronegative healthy controls but the total immunocyte number per mucosal section length unit (500 μm) was significantly increased in patients (median 175 v 120 cells/unit; p<0.008), mainly comprised of IgA (p<0.02) and IgG1 (median 81.8% of total IgG; p<0.02) isotypes. Patients receiving a successful HAART regimen tended to normalise their IgG1 proportion and showed significantly lower total duodenal IgA immunocyte number than those receiving no or insufficient antiretroviral treatment (p<0.005). Conclusion: Our study demonstrated that advanced AIDS patients hyperactivate their intestinal B cell system. HAART could significantly reverse this perturbation, suggesting restored ability of the mucosal immune system to control intestinal infections.